'Hall-Petch' type of relationship between the extent of intergranular corrosion and grain size in a Ni-based superalloy. (October 2020) - Kaithwas, C.K.; Bhuyan, P.; Pradhan, S.K.; Mandal, Sumantra
Graphical abstract: Highlights: A range of grain sizes is obtained without varying other microstructural attributes. Effect of a spectrum of grain sizes on intergranular corrosion was investigated. Sensitization-desensitization phenomenon is delayed in the coarse-grained specimens. Hall-Petch type relation is observed between DOS (also weight loss) and grain size. DOS (and weight loss) varies inversely proportional to the (grain size) 1/4 . Abstract: The present work elucidates the individual implication of wide spectrum of grain size on degree of sensitization (DOS) and intergranular corrosion in alloy 600H. Experimental evidences suggest that both the sensitization and desensitization phenomena are significantly delayed in the coarse-grained specimens. This is attributable to the lower driving force available in the coarser grains for the diffusion of Cr from the grain to the boundary. Interestingly, a Hall-Petch type relation has been observed between DOS (as well as weight loss) and grain size in which both the DOS and weight loss varied inversely proportional to the (grain size) 1/4 .